2021
DOI: 10.3389/fpsyg.2021.765754
|View full text |Cite
|
Sign up to set email alerts
|

An MRI Study on Effects of Math Education on Brain Development Using Multi-Instance Contrastive Learning

Abstract: This paper explores whether mathematical education has effects on brain development from the perspective of brain MRIs. While biochemical changes in the left middle front gyrus region of the brain have been investigated, we proposed to classify students by using MRIs from the intraparietal sulcus (IPS) region that was left untouched in the previous study. On the cropped IPS regions, the proposed model developed popular contrastive learning (CL) to solve the problem of multi-instance representation learning. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Studies have shown that mathematics education is associated with IPS and MFG regions [ 3 ]. In our previous work [ 31 ], we proposed MiCL to study the influence of the intraparietal Sulcus (IPS) region on mathematics education. This work analyzes how the MFG area affects students’ mathematics education.…”
Section: Discussion and Conclusionmentioning
confidence: 99%
“…Studies have shown that mathematics education is associated with IPS and MFG regions [ 3 ]. In our previous work [ 31 ], we proposed MiCL to study the influence of the intraparietal Sulcus (IPS) region on mathematics education. This work analyzes how the MFG area affects students’ mathematics education.…”
Section: Discussion and Conclusionmentioning
confidence: 99%
“…At individual level, Mathematics supports analytical thinking and logical reasoning processes, improves problem-solving skills, and enhances critical thinking and creativity (Hagan et al, 2020). Mathematical learning has been linked to significant improvements in the brain's plasticity, various cognitive functions, emotional health, overall life quality, and development indices (Zhang et al, 2021). Besides, Mathematics knowledge is essential for the learning of many other subjects, opens multiple career paths to an individual, and is a pre-requisite for several courses.…”
Section: Introductionmentioning
confidence: 99%